2015
DOI: 10.1186/s13030-015-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and major adverse cardiovascular and cerebrovascular events in patients following coronary artery bypass graft surgery: a five year longitudinal cohort study

Abstract: BackgroundAlthough depression and anxiety have been implicated in risk for major adverse cardiovascular and cerebrovascular events (MACCE), a theoretical approach to identifying such putative links is lacking. The objective of this study was to examine the association between theoretical conceptualisations of depression and anxiety with MACCE at the diagnostic and symptom dimension level.MethodsBefore coronary artery bypass graft (CABG) surgery, patients (N = 158; 20.9 % female) underwent a structured clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 81 publications
1
56
1
3
Order By: Relevance
“…Though one study found that GAD was protective in the post-ACS period [21], most studies suggest that GAD is associated with poor cardiac health in all stages of CAD [22-24]. Following myocardial infarction (MI), GAD has been linked to a nearly two-fold increased risk of mortality over the subsequent ten years [23], and in patients with stable CAD, GAD is associated with a two-fold increased risk of major adverse cardiac events over the next two years [22].…”
Section: Anxiety Disorders In Patients With Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Though one study found that GAD was protective in the post-ACS period [21], most studies suggest that GAD is associated with poor cardiac health in all stages of CAD [22-24]. Following myocardial infarction (MI), GAD has been linked to a nearly two-fold increased risk of mortality over the subsequent ten years [23], and in patients with stable CAD, GAD is associated with a two-fold increased risk of major adverse cardiac events over the next two years [22].…”
Section: Anxiety Disorders In Patients With Cardiovascular Diseasementioning
confidence: 99%
“…Following myocardial infarction (MI), GAD has been linked to a nearly two-fold increased risk of mortality over the subsequent ten years [23], and in patients with stable CAD, GAD is associated with a two-fold increased risk of major adverse cardiac events over the next two years [22]. In a prospective study of 158 patients undergoing CABG surgery, GAD was associated with incident major adverse cardiac events over the subsequent 5 years [24]. The associations between GAD and outcomes in HF have not yet been studied.…”
Section: Anxiety Disorders In Patients With Cardiovascular Diseasementioning
confidence: 99%
“…Je napovedni dejavnik za slabšo napoved izida (32). Bolniki z anksioznostjo pred posegom so imeli večje tveganje za smrtnost (32,33), subjektivno poslabšanje, senzorično bolečino in telesne simptome 12 mesecev po operaciji (34). Pooperativna anksioznost naj bi bila prav tako dejavnik tveganja za višjo smrtnost, akutni miokardni infarkt in ponavljajoče se hospitalizacije (34,35).…”
Section: Spl-pop -Splošna Populacija Kb -Koronarna Bolezen Srca Pciunclassified
“…Было включено 142 пациента (сред-рисков развития ОКС было ОР=1,52 (95% ДИ 1,36-1,71) по показателю тревоги, независимо от других факторов риска [2]. Риск "больших нежелательных сердечно-сосудистых событий" (МАСЕ) повыша-ется при наличии тревоги после операции аорто-коронарного шунтирования (ОР=2,79; 95% ДИ 1,00-7,80) (Tully, et al, 2015) [3]. Belan, et al (2015) также указывают на неблагоприятное влияние ситуатив-ной тревожности у пациентов после аорто-коронар-ного шунтирования [4].…”
Section: враждебность тревожность и жизненное истощение в патогенезеunclassified